2017
DOI: 10.1002/jcb.25920
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of G1691S Variant in the Human Filamin B Gene Responsible for Larsen Syndrome: A Comparative Computational Approach

Abstract: Larsen syndrome (LRS) is a rare genetic disease associated with variable manifestations including skeletal malformations, dislocations of the large joints, and notable changes in facial and limb features. Genetic variants in the Filamin B (FLNB) gene are associated with the development of LRS. We searched two literature databases (OMIM and PubMed) and three gene variant databases (HGMD, UniProt, & dbSNP) to capture all the possible variants associated with LRS phenotype, which may have an impact on the FLNB fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Hence RMSD analyses were carried out for the BA6753 in the presence of fosfomycin as well as the 19583672. This lesser the radius of gyration elucidates the system had higher compactness and vice versa [Sneha et al, 2017]. Equilibration of RMSD values is depicted in Figure 2.…”
Section: Molecular Simulation Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…Hence RMSD analyses were carried out for the BA6753 in the presence of fosfomycin as well as the 19583672. This lesser the radius of gyration elucidates the system had higher compactness and vice versa [Sneha et al, 2017]. Equilibration of RMSD values is depicted in Figure 2.…”
Section: Molecular Simulation Analysismentioning
confidence: 89%
“…From the graph, it is clear that BA6753 with 19583672 showed lower Rg values than with the fosfomycin, indicating the little conformational changes throughout the simulation. This lesser the radius of gyration elucidates the system had higher compactness and vice versa [Sneha et al, 2017]. Hydrogen bond interactions play a crucial role in the overall stability of the protein structure.…”
Section: Molecular Simulation Analysismentioning
confidence: 95%
“…Furthermore, the identification of likely pathogenic variants in patients with CD was mainly based on in silico analyses. Although the use of multiple computational prediction tools boosts the reliability of variant classification in many diseases (Pasupati et al, 2017; Zaki et al, 2017), the current study still lacks experimental evidence to verify their contributions to the pathogenesis of CDs. Therefore, further functional investigations focused on specific mutations are required to elucidate the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the four missense mutations were also confirmed using PredictSNP (Bendl et al., 2014), and istable (Chen et al., 2013) tools. Moreover, in previous studies relation of missense mutations to other diseases has been also reported (Ali et al., 2017; P et al., 2017).…”
Section: Resultsmentioning
confidence: 81%